Telluride-bearing Au-Ag mineralization in the Singu-Tabeikkyin gold District, Mogok metamorphic Belt, Myanmar: New constraints on an intermediate-sulfidation epizonal orogenic ore system. (15th April 2022) - Zaw Myint, Aung; Wagner, Thomas; Zaw, Khin
Graphical abstract: Highlights: Fluid inclusion microthermometric measurements yielded formation temperatures ranging from 180 to 310 °C. Native gold, hessite, and tellurobismuthite were formed at conditions of logƒTe2 of − 17 to − 9.5, and logƒS2 of − 13.4 to − 12.5 at 250 °C. Te-bearing Au-Ag mineralization was part of an intermediate-sulfidation epizonal orogenic Au system. Abstract: The Singu-Tabeikkyin gold district is located in the Mogok Metamorphic Belt in Myanmar. Gold mineralization in this district occurs in a set of mainly N − S trending quartz veins, which are associated with minor replacement zones and skarns. This study investigates the field geology, ore mineralogy, mineral chemistry, and fluid inclusion characteristics of three gold prospects (CG-1, CG-2, and CG-3) containing Au-Ag along with telluride assemblages. Gold has formed as two generations, and only the second gold mineralization stage is associated with major telluride assemblages. The tellurides are associated with chalcopyrite, a late generation of sphalerite, and electrum. The telluride phases identified in the study are hessite (Ag2 Te), petzite (Ag2 AuTe3 ), altaite (PbTe), tellurobismuthite (Bi2 Te3 ), and tetradymite (Bi2 Te2 S), and unnamed Au-Ag telluride phases. Liquid-rich two-phase fluid inclusions have homogenization temperatures in the range of 174–310 °C, and salinities of 1–12 wt% NaCl equiv. The chlorite geothermometry in this study yielded a variable temperature range from as low as 250 °C to 380 °C, in general agreement with the fluid inclusion temperature range. The thermometric data, in conjunction with the analysis of telluride-sulfide phase stability, constrain the conditions of ore formation to logƒTe2 and logƒS2 values of − 17 to − 9.5, and of − 13.4 to − 12.5. The geological and mineralogical data and the reconstructed conditions of ore formation as well as high-grade metamorphic host rocks of gneiss, marble and calc-silicates suggest that the telluride bearing gold-silver mineralization in the Singu-Tabeikkyin gold district forms part of an intermediate-sulfidation epizonal orogenic Au system.